Pengaruh ROA, ROE, DER dan EPS Terhadap Harga Saham Pada Perusahaan Advertising, Printing Dan Media Yang Terdaftar di BEI - Saria Sinaga; Abdul Rahman (Politeknik Ganesha Medan, 2024)
The conditions found are that in 2021 and 2022, there was an increase in the average ROA value, but the stock price decreased and the average ROE value in 2019 and 2020 increased, but the stock price actually decreased. This is contrary to the theory which states that the higher the ROA and ROE, the better the company's performance which should attract investors and increase stock prices. This study aims to analyze the Effect of Return on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER) and Earnings Per Share (EPS) on stock prices in Advertising, Printing and Media sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2022. This study uses secondary data with a quantitative approach. The analysis method used in this study is multiple linear regression with simultaneous and partial testing. The results of the study show that simultaneously, the variables ROA, ROE, DER, and EPS do not have a significant effect on stock prices. Partially, each independent variable also does not have a significant effect on stock prices. The Adjusted R Square value in this study is 0.099 or 9.9%, which indicates that the ROA, ROE, DER, and EPS variables together are only able to explain 9.9% of stock price variations, while the remaining 90.1% is influenced by other factors not included in this research model. These results indicate that the variables used in this study have a less strong influence on stock prices in the Advertising, Printing and Media sector